2019
DOI: 10.1002/aenm.201900516
|View full text |Cite|
|
Sign up to set email alerts
|

Identifying Catalytic Active Sites of Trimolybdenum Phosphide (Mo3P) for Electrochemical Hydrogen Evolution

Abstract: candidates to replace precious metal catalysts owing to the unique electronic properties of their edge structures. [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] However, the basal plane of these catalysts containing substantial amount of their surface structure remains nearly inactive making these catalysts inefficient, especially for practical applications. [26][27][28][29] Therefore, designing and developing a new class of nonprecious metal catalysts with an increased intrinsic activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 51 publications
(31 citation statements)
references
References 59 publications
1
30
0
Order By: Relevance
“…i) HER volcano plot obtained from plotting exchange current density concerning Gibbs free energy of adsorbed hydrogen on various samples. Reproduced with permission . Copyright 2019, John Wiley and Sons.…”
Section: Modulated Strategies For Tmps In Electrocatalytic Her Oer mentioning
confidence: 99%
See 2 more Smart Citations
“…i) HER volcano plot obtained from plotting exchange current density concerning Gibbs free energy of adsorbed hydrogen on various samples. Reproduced with permission . Copyright 2019, John Wiley and Sons.…”
Section: Modulated Strategies For Tmps In Electrocatalytic Her Oer mentioning
confidence: 99%
“…Nevertheless, when we jump to the conclusion that lower M/P stoichiometric ratios in TMPs are better for HER, this issue becomes controversial again. More recently, Asadi and co‐workers reported that tri‐molybdenum phosphide (Mo 3 P) nanoparticles presented a better HER activity than that of phosphorus‐rich MoP from practical experiment and theoretical calculation . Typically, Mo 3 P adopted the tetragonal structure with each Mo atom is coordinated by either two or four P atoms, while MoP crystallized in hexagonal structure with Mo six‐coordinated by P atoms.…”
Section: Modulated Strategies For Tmps In Electrocatalytic Her Oer mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, we have demonstrated that trimolybdenum phosphide (Mo 3 P) nanoparticles can be a promising catalyst candidate, owing to its unique structure; its surface provides a high density of molybdenum (Mo) active sites with special electronic properties, that is, low work function and high density of d‐orbital electrons at Fermi energy, which can be promising for electrocatalysis. [ 21 ] The important role of surface reconstructions in catalysis, which renders the surface region of the catalyst atomically and geometrically distinct relative to the bulk, has been pointed out. [ 22,23 ] A special type of surface reconstructions that can happen in an oxygen‐rich environment is the formation of ultrathin oxide overlayers.…”
Section: Figurementioning
confidence: 99%
“…The ORR is of pivotal significance for fuel cells and metal-air batteries. Similarly, the HER through electrocatalytic water splitting is considered as a promising approach to the production of clean hydrogen [112][113][114]. Recently, several research groups have studied the metal-atom-anchored GDY catalysts for HER electrocatalysis applications with the support of theoretical calculations.…”
Section: Metal-atom-anchored Gdy Electrocatalystsmentioning
confidence: 99%